E-068 Assessment of cell yield among different devices for endovascular biopsy to harvest endothelial cells. (23rd July 2017) - Alexander, M; Darflinger, R; McGregor, H; Conrad, M; Sun, Z; Cooke, D
Abstract : Introduction/Purpose: Routine surgical collection of vessels limits pathophysiological understanding of vascular disorders, particular those of the central nervous system. This problem in turn slows the development of diagnostic techniques and therapies. To address this issue, endovascular biopsy techniques have been developed and validated. To refine these techniques, we compared device performance as it relates to the yield of endothelial cells (ECs) harvested from vessels. Materials and methods: Cell harvesting procedures performed initially in rabbits and subsequently in humans were analyzed. The number of ECs sampled during each procedure along with subject, device, and technical features were tabulated. Species was noted, as was disease state interrogated, if any. Diseases present included aneurysm, arteriovenous malformation, and extra- and intracranial atherosclerosis. Locations sampled were classified as intracranial, extracranial, and body. Devices from which ECs were sampled included microwires, angioplasty balloons, stent delivery catheters, coils, Phenox clot retriever (PCR), retrievable stents, and vascular plug devices. For devices with roughly cylindrical shape that contacts the vessel wall (balloons, PCRs, stentrievers), the number of cells harvested per square mm was calculated by the equation, cells/(π*width*length). Chi-square analysis was performed to compare means of ECs harvested between the above-listed variables. Results: 70 sampling procedures were performed, 33 in rabbits and 37 in humans. Normal vessels were sampled in 25 cases. ECs were sampled in 24 aneurysms, 14 arteriovenous malformations, 4 extracranial atherosclerotic lesions, and 3 intracranial plaques. Mean ECs collected by device type are summarized in Table 1. No differences were found for species, location, or pathology. PCRs and stentrievers yielded more ECs than other types of devices, χ²(1, N = 70) = 55.06, p = 0.001. Among cylindrical devices, no difference was noted in EC yield or EC/mm 2 . PCR devices were deployed in vessels with smaller diameters (1-3 mm) compared to balloons and stentrievers (4-8 mm). Conclusion: Among devices studied for EC harvesting, PCRs and stentrievers yield more cells than other devices. PCRs appear more suitable for harvesting ECs in small vessels, while stentrievers are better for harvesting from large vessels. Further study of these devices for EC sampling is warranted to initiate and refine its use in humans for this purpose. Disclosures: M. Alexander: 1; C; Joe Niekro Foundation Research Award. R. Darflinger: None. H. McGregor: None. M. Conrad: None. Z. Sun: None. D. Cooke: 1; C; SNIS Foundation Research Grant, Joe Niekro Research Grant.